The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.bioconjchem.5b00191
|View full text |Cite
|
Sign up to set email alerts
|

HaloTag Technology: A Versatile Platform for Biomedical Applications

Abstract: Exploration of protein function and interaction is critical for discovering links between genomics, proteomics, and disease state; yet the immense complexity of proteomics found in biological systems currently limit our investigational capacities. While affinity and autofluorescent tags are widely employed for protein analysis, these methods have limited success as they lack specificity and require multiple fusion tags and genetic constructs. As an alternative approach, the innovative HaloTag protein fusion pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
209
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(224 citation statements)
references
References 131 publications
(260 reference statements)
3
209
0
Order By: Relevance
“…Because green fluorescent protein (GFP) imported into the mitosome matrix is not fluorescent [23], GFP-tagging of mitosomes has not been possible until now. Martinkova et al [59] have shown that mitosomes in trophozoites can be labeled for live cell microscopy using HaloTag markers [60]. However, no quantitative information on the spatial dynamics of peripheral mitosomes in the cytoplasm was presented in this report.…”
Section: Resultsmentioning
confidence: 92%
“…Because green fluorescent protein (GFP) imported into the mitosome matrix is not fluorescent [23], GFP-tagging of mitosomes has not been possible until now. Martinkova et al [59] have shown that mitosomes in trophozoites can be labeled for live cell microscopy using HaloTag markers [60]. However, no quantitative information on the spatial dynamics of peripheral mitosomes in the cytoplasm was presented in this report.…”
Section: Resultsmentioning
confidence: 92%
“…Another novel technology called the HaloTag fusion tag, allowed for rapid evaluation of several potential fluorophores. 47 The HaloTag system is based on the formation of a stable fusion protein that carries an active site for binding of application-specific ligands. This results in a covalent interaction between the HaloTag-tagged protein and specific ligand.…”
Section: Applications Of the Nanoluc Technologymentioning
confidence: 99%
“…So far, the HaloTag is mainly used for various biomedical applications, e.g. the in vivo detection of protein interactions and cell imaging (Los et al, 2008;England et al, 2015). In 2010, an initial study of this tag for biocatalysis was published using a monomeric lipase from Bacillus thermocatenulatus bound to magnetic beads.…”
Section: Introductionmentioning
confidence: 99%